2019
DOI: 10.1021/acs.est.8b06377
|View full text |Cite
|
Sign up to set email alerts
|

Polyzwitterionic Hydrogels in Engines Based on the Antipolyelectrolyte Effect and Driven by the Salinity Gradient

Abstract: In this paper, we propose and investigate an original approach to energy conversion based on polyzwitterionic hydrogels, which exhibit an antipolyelectrolyte effect that enables them to swell in salt water and shrink in water of a different (i.e., desalinated water) salinity. The swelling and shrinking processes run cyclically and can move a piston up or down reversibly, thus transforming the antipolyelectrolyte effect into a mechanical force based on the salinity gradient. This phenomenon makes polyzwitterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The change in mechanical properties can significantly influence the biocompatibility and processability of materials. Studying the effect of electrical fields and pH not only provides control and tunable material properties but also elucidates the response of microcapsules and hydrogels to electric field and pH, which can be applied in biotechnological process requiring electrochemical reaction [46], smart robotics [47], energy production [48], and water separation processes [49].…”
Section: Resultsmentioning
confidence: 99%
“…The change in mechanical properties can significantly influence the biocompatibility and processability of materials. Studying the effect of electrical fields and pH not only provides control and tunable material properties but also elucidates the response of microcapsules and hydrogels to electric field and pH, which can be applied in biotechnological process requiring electrochemical reaction [46], smart robotics [47], energy production [48], and water separation processes [49].…”
Section: Resultsmentioning
confidence: 99%
“…The alternative of using hydrogels to convert salinity gradient energy into mechanical energy has been introduced in recent years [29][30][31][32]. High and low salinity solutions alternatingly flow through a hydrogel, which is placed in a modified syringe operating in a piston-type process.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have the advantage of being cheap, easier to keep, and are more controllable than membrane-based technologies. The first studied hydrogels for this application was poly(acrylic acid) [29,30]; later, poly(allylamine hydrochloride) [31] and zwitterionic polysulfobetaine [32] hydrogels have been examined. It has been found that the energy efficiency decreases with increasing particle size [29,32] and goes through a maximum as the crosslinking density [30][31][32] or external load [29][30][31] is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betaines as derivatives with a zwitterionic nature are named according to their negatively charged moieties such as carboxybetaine, sulfobetaine, and phosphobetaine covalently linked to positively charged quaternary ammonium moieties within one molecule. Modification with such derivatives has been utilized widely by others and by us in order to improve performance and operational parameters of biosensors (Bertok et al, 2013 , 2015 ), for protein stabilization (Kasák et al, 2016 ; Liu and Jiang, 2016 ), to develop blood-compatible materials (Chocholova et al, 2018 ) and for other advanced applications (Ilčíková et al, 2015 ; Zavahir et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%